Mengharmoniskan Asas Praduga Tak Bersalah dan Kehadiran di Persidangan: Rekonstruksi Hukum Acara Pidana dengan Pengawasan Elektronik - Erwin Susilo (Jurnal Ilmiah Kebijakan Hukum, 2025)
This study offers a normative reconstruction of the Indonesian Criminal Procedure Code (KUHAP) to explicitly regulate electronic monitoring devices as the least restrictive alternative to conventional detention, ensuring defendants’ presence in court while upholding the presumption of innocence. The research employs a juridical-normative method through statutory, conceptual, and comparative-functional approaches. The analysis covers KUHAP, its implementing regulations, the 2025 Draft KUHAP, and the Prosecutor’s Guideline No. 4 of 2023, compared with practices in England, the United States, Australia (New South Wales), and Jordan. The findings reveal a legal gap, as KUHAP does not yet regulate electronic monitoring, and its application currently relies on internal prosecutorial guidelines lacking normative legitimacy and judicial oversight. Comparative analysis demonstrates that electronic monitoring—particularly GPS-based systems—effectively reduces defendants’ failure to appear, mitigates prison overcrowding, and reinforces due process of law through individualized risk assessment and proportionality testing. The study recommends the explicit inclusion of electronic monitoring within KUHAP as a mechanism to be applied only through judicial determination, supported by clear operational standards, periodic evaluations, privacy protection, and state funding. Integrating electronic monitoring into KUHAP will balance the efficiency of law enforcement with the protection of human rights. This study’s novelty lies in proposing the explicit incorporation of electronic monitoring into the Indonesian Criminal Procedure Code as a normative reconstruction at the trial stage